Rational and Design of the SIMULATOR Study: A Multicentre Randomized Study to Assess the Impact of SIMULation-bAsed Training on Transoesophageal echocardiOgraphy leaRning for Cardiology Residents - Pezel, Théo; Bernard, Anne; Lavie Badie, Yoan; Dreyfus, Julien; Audureau, Etienne; Bohbot, Yohann; Fard, Damien; Hubert, Arnaud; Nguyen, Lee S.; Monteil, Cécile; Bière, Loïc; Le Ven, Florent; et al. (Frontiers in Cardiovascular Medicine, 2021)
Introduction: Simulation-based training in transesophageal echocardiography (TEE) seems promising. However, data are limited to non-randomized or single-center studies. To assess the impact of simulation-based vs. traditional teaching on TEE knowledge and performance for medical residents in cardiology. Materials and Methods: Nationwide prospective randomized multicenter study involving 43 centers throughout France allowing for the inclusion of >70% of all French cardiology residents. All cardiology residents naive from TEE will be included. Randomization with stratification by center will allocate residents to either a control group receiving theoretical knowledge by e-learning only, or to an intervention group receiving two simulation-based training sessions on a TEE simulator in addition. Results: All residents will undergo both a theoretical test (0–100 points) and a practical test on a TEE simulator (0–100 points) before and 3 months after the training. Satisfaction will be assessed by a 5-points Likert scale. The primary outcomes will be to compare the scores in the final theoretical and practical tests between the two groups, 3 months after the completion of the training. Conclusion: Data regarding simulation-based learning in TEE are limited to non-randomized or single-center studies. The randomized multicenter SIMULATOR study will assess the impact of simulation-based vs. traditional teaching on TEE knowledge and performance for medical residents in cardiology, and whether such an educational program should be proposed in first line for TEE teaching.